Whey protein hydrolysate supplementation accelerates recovery from exercise-induced muscle damage in females - Brown, M. A.; Stevenson, E. J.; Howatson, G. (Applied Physiology, Nutrition, and Metabolism, 2018)
A number of different forms of protein and their analogues have been investigated for their efficacy in ameliorating exercise-induced muscle damage (EIMD) and recovery. Preliminary data regarding whey protein hydrolysate (WPH) supplementation are promising. However, its efficacy beyond acute eccentric/resistance exercise bouts or longer term training programmes are limited and all investigations have been conducted in male or mixed-sex groups. This study sought to elucidate whether the benefits of WPH previously reported can be demonstrated in females following repeated-sprint exercise. Twenty physically active females were assigned to consume 2 doses of 70 mL WPH or isoenergetic carbohydrate (CHO) for 4 days post-EIMD. Measures of muscle soreness, limb girth, flexibility, muscle function, and creatine kinase were collected before, immediately after, and 24, 48, and 72 h postexercise. Time effects were observed for all variables (p < 0.05) except limb girth, which is indicative of EIMD. Flexibility improved beyond baseline measures following WPH by 72 h, but had failed to recover in the CHO group (p = 0.011). Reactive strength index was higher throughout recovery in the WPH group compared with CHO (p = 0.016). Reductions in creatine kinase were greater following WPH compared with CHO at 48 h post-EIMD (p = 0.031). The findings suggest that 4-day supplementation of WPH is beneficial for reducing symptoms of EIMD and improving recovery of muscle function in physically active females.